Readiness to Refrain from Carbonated Drinks among High School Female Students: The Transtheoretical Model of Change as a Theoretical Framework - Hawraa Kareem Abed Ali, Wissam Jabbar Qasim, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: This study is a part of randomized controlled trial. This study aims to identify high school female students’ readiness to refrain from carbonated drinks. Method: The study included a simple random sample of 144 high school female students who were recruited from Al-Russafa High School for females in Baghdad City. The study instrument consists of participants’ sociodemographic characteristics of age, living arrangement, and family’s socioeconomic status, Stages of Change for Carbonated Drinks Consumption Behavior Scale (Short Form), Stages of Change for Carbonated Drinks Consumption Behavior Scale (Continuous Measure), The Processes of Change for Carbonated Drinks Consumption Behavior Scale, The Self-Efficacy for Carbonated Drinks Consumption Behavior Scale which includes 18 Decisional Balance Scale for Carbonated Drinks Consumption Behavior. Data were analyzed using the statistical package for social science (SPSS) for Windows, version 26. Results: More than half are in the Precontemplation Stage of Change (n = 84; 58.3%), followed by those who are in the Preparation Stage of Change (n = 30; 20.8%), those who are in the Contemplation Stage of Change (n = 28; 19.5%), and those who are in the Maintenance Stage of Change (n = 2; 1.4%).The regression model displays that the family’s socioeconomic status, Self-Liberation, and students’ age positively predicted the Stages of Change to refrain from carbonated drinks (p-value = .004, .009, 035) respectively. Conclusion: The regression model displayed that Self-Liberation and students’ age positively predicted the Stages of Change to refrain from carbonated drinks. This finding implies that .The regression model displayed that students’ age positively predicted the Stages of Change to refrain from carbonated drinks. Keywords: Carbonated Drinks; Readiness to Refrain; High School Female Students.